2021
DOI: 10.3390/a15010005
|View full text |Cite
|
Sign up to set email alerts
|

Deep Transfer Learning for Parkinson’s Disease Monitoring by Image-Based Representation of Resting-State EEG Using Directional Connectivity

Abstract: Parkinson’s disease (PD) is characterized by abnormal brain oscillations that can change rapidly. Tracking neural alternations with high temporal resolution electrophysiological monitoring methods such as EEG can lead to valuable information about alterations observed in PD. Concomitantly, there have been advances in the high-accuracy performance of deep neural networks (DNNs) using few-patient data. In this study, we propose a method to transform resting-state EEG data into a deep latent space to classify PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Utilizing the orthogonalized directed coherence (gOPDC) enumerating the directional connectivity (DC) between the pairwise EEG channels among the quartet frequency (θ,α,β, and γ) and visualizing the calculated DCs into 2D plots as the input to the selected network of VGG-16 (as the pre-trained model). It achieved the accuracy of 99.62% with precision 100% and recall of 99.17% along with 0.9958 of F1-score, and the AUC averaged over 10 repetitive instances of training proffers 0.9958 [25].…”
Section: Literature Reviewmentioning
confidence: 94%
“…Utilizing the orthogonalized directed coherence (gOPDC) enumerating the directional connectivity (DC) between the pairwise EEG channels among the quartet frequency (θ,α,β, and γ) and visualizing the calculated DCs into 2D plots as the input to the selected network of VGG-16 (as the pre-trained model). It achieved the accuracy of 99.62% with precision 100% and recall of 99.17% along with 0.9958 of F1-score, and the AUC averaged over 10 repetitive instances of training proffers 0.9958 [25].…”
Section: Literature Reviewmentioning
confidence: 94%
“…In our study, we utilized the VGG-16 architecture [ 23 ], which was pre-trained on the ImageNet dataset, including 1.2 million images. We only used the weights of convolutional layers from the pre-trained model.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the primary layers of a Deep Convolutional Neural Network (DCNN) trained on a vast data set can extract generic features [ 20 , 21 ]. One favorable network in literature for transfer learning is the VGG-16 architecture [ 22 ] trained on the ImageNet dataset pre-trained model [ 23 ]. It has already been shown that the VGG-16 network is able to extract informative features for vital signs (HR/RR) estimation among adults [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transfer learning, which also provided a latent space that is more strongly related to clinical indices, produced excellent classification performance. According to the research of [185], a heatmap-integrated image classifier combined with transfer learning may provide a way to classify small sample datasets. The effectiveness of the classifier and research methodology will be further improved.…”
Section: Transfer Learningmentioning
confidence: 99%